Interleukin 35: A Key Mediator of Suppression and the Propagation of Infectious Tolerance - Olson, Brian M.; Sullivan, Jeremy; Burlingham, William (Frontiers in Immunology, 2013)
The importance of regulatory T cells in balancing the effector arm of the immune system is well documented, playing a central role in preventing autoimmunity, facilitating graft tolerance following organ transplantation, and having a detrimental impact on the development of anti-tumor immunity. These regulatory responses use a variety of mechanisms to mediate suppression, including soluble factors. While IL-10 and TGF-β are the most commonly studied immunosuppressive cytokines, the recently identified IL-35 has been shown to have potent suppressive function in vitro and in vivo. Furthermore, not only does IL-35 have the ability to directly suppress effector T cell responses, it is also able to expand regulatory responses by propagating infectious tolerance and generating a potent population of IL-35-expressing inducible regulatory T cells. In this review, we summarize research characterizing the structure and function of IL-35, examine its role in disease, and discuss how it can contribute to the induction of a distinct population of inducible regulatory T cells.